Rebozo technique to decrease pain intensity and length of labor - Sarli, Desi; Putri, Arfianingsih Dwi (Universitas Muhammadiyah Purwokerto, 2024)
Background: Pain and length of labor impact the mother physically and psychologically. Both of these factors must be minimized to avoid complications during labor. In Indonesia, the rebozo technique is still rarely performed by health workers such as midwives, especially in West Sumatra.Objective: This study aims to determine the effect of the rebozo technique on reducing pain intensity and duration of labor in primiparas.Method: This is a quasi-experimental study with a two-group design. Sixty primiparous mothers were randomly divided into two groups (intervention and control groups). The intervention group received the rebozo technique, and the control group received standard treatment. The pain intensity and duration of labor were observed throughout the study. Data analysis used the independent t-test.Results: The study showed that the average pain intensity in the intervention group was lower than the control group (6.423 vs 7.562, p <0.05). The average duration of labor was faster in the intervention group than in the control group (3.643 vs 4.815, p <0.0001).Conclusion: The rebozo technique is effective in reducing pain and accelerating labor.